Macrophage Activities in Myocardial Infarction and Heart Failure - Sophia Esi Duncan; Shan Gao; Michael Sarhene; Joel Wake Coffie; Deng Linhua; Xingru Bao; Zhang Jing; Sheng Li; Rui Guo; Jing Su; Guanwei Fan (Cardiology Research and Practice)
Heart diseases remain the major cause of death worldwide. Advances in pharmacological and biomedical management have resulted in an increasing proportion of patients surviving acute heart failure (HF). However, many survivors of HF in the early stages end up increasing the disease to chronic HF (CHF). HF is an established frequent complication of myocardial infarction (MI), and numerous influences including persistent myocardial ischemia, shocked myocardium, ventricular remodeling, infarct size, and mechanical impairments, as well as hibernating myocardium trigger the development of left ventricular systolic dysfunction following MI. Macrophage population is active in inflammatory process, yet the clear understanding of the causative roles for these macrophage cells in HF development and progression is actually incomplete. Long ago, it was thought that macrophages are of importance in the heart after MI. Also, though inflammation is as a result of adverse HF in patients, but despite the fact that broad immunosuppression therapeutic target has been used in various clinical trials, no positive results have showed up, but rather, the focus on proinflammatory cytokines has proved more benefits in patients with HF. Therefore, in this review, we discuss the recent findings and new development about macrophage activations in HF, its role in the healthy heart, and some therapeutic targets for myocardial repair. We have a strong believe that there is a need to give maximum attention to cardiac resident macrophages due to the fact that they perform various tasks in wound healing, self-renewal of the heart, and tissue remodeling. Currently, it has been discovered that the study of macrophages goes far beyond its phagocytotic roles. If researchers in future confirm that macrophages play a vital role in the heart, they can be therapeutically targeted for cardiac healing.